WHEN PERFORMING SOME COMPUTATIONS RELATED TO ARCFUNCTIONS - O. Makhmudova (Galaxy International Interdisciplinary Research Journal, 2023)
theoretical information is provided about performing some calculations related to arcfunctions by applying the field of function values, and the necessary examples are solved.